The Habits of Mind by 10th Grade High School Student - Tara Hunar Ahmed; Farhad Ali Mustafa; Bakhtiar Kakil Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The aim of this study is to know the level of knowledge (Habits of Mind by 10th grade high school students). To achieve the goal, the researchers put forward the following hypothesis: 1. There is no statistically significant difference in the level of error ratio (0.05≥α) at the level of habits of mind according to the variables in research (gender), (male, female). The research sample includes 10th grade students some schools namely (Wani for Boys – Rhubarb for Girls - Barzani Namr for Boys- Nanakali for Girls - Ahmadi Khani for Boys), which includes 240 students, 120 female students, and 120 male students. To achieve the research's objectives and assumptions, the researchers have developed a tool: - It was the criterion of habits of mind, which researchers relied on the (Asma Hassan 2013) scale, which consisted of eight habits: (Right Thinking - Interesting and Heartfelt Response - Inventing, Imagining and producing - Applying Past Knowledge to New Situations - Managing Impulsivity - Remaining Open to Continuous Learning - Gathering Data Through all Senses - Thinking Interdependently), it was 129 items, the researchers used (Cronbach Alpha) equation to stabilize the scale, the rate was 0.925, it made everything at an acceptable level. This procedure begun in the second semester on 1 February 2021 and continued till (2022/2/20). In order to Analyze the result, the researchers used SPSS Statistics The result was as follows: - The absence of statistical function differences at the level (0.05) at the level of ownership of habits of mind according to gender variable (male and female), except for (reckless control) means statistical meaning at a level (0.05) for male interest.